A practice-oriented framework for basic life support training of Brazilian school teachers: integrating Law 13,722/2018, andragogy, and the health belief model - Carvalho Castanha, Cyntia Souza; Guerrero Daboin, Blanca Elena; Zangirolami-Raimundo, Juliana; Barbosa Tavares, Luis Fernando; de Abreu, Luiz Carlos; Raimundo, Rodrigo Daminello (Frontiers in Public Health, 2025)
The importance of immediate cardiopulmonary resuscitation (CPR) and proper use of automated external defibrillators in increasing survival rates for cardiac arrest victims is well established. Expanding public access to CPR training and promoting timely emergency response can significantly improve outcomes. Although various global initiatives exist, the inclusion of CPR training in Brazilian school curricula remains limited. The enactment of Law 13,722 in October 2018 marked a major legislative milestone, mandating first aid training for staff in all schools and child recreational facilities as of March 2019. However, implementation challenges persist across Brazil’s diverse and expansive territory. This paper introduces a structured educational framework for Basic Life Support training, incorporating the first three components of the Chain of Survival: recognizing cardiac arrest, activating emergency services, and delivering high-quality CPR. Grounded in Andragogy and the Health Belief Model, the framework emphasizes adult learning principles while enhancing teachers’ knowledge, motivation, self-efficacy, and readiness to act. To support program design and scalability, a Logic Model (resources-to-outcomes map) outlines key implementation steps, while the CIPP model is proposed for monitoring and evaluation. This integrated approach provides a practical, adaptable foundation for implementing school-based emergency preparedness across Brazil, while also creating a scalable pathway that could extend benefits to the broader community through increased CPR readiness.